The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41417-021-00399-1
|View full text |Cite
|
Sign up to set email alerts
|

Can gene therapy be used to prevent cancer? Gene therapy for aldehyde dehydrogenase 2 deficiency

Abstract: Approximately 8% of the world population and 35 to 45% of East Asians are carriers of the hereditary disorder, aldehyde dehydrogenase 2 (ALDH2) deficiency. ALDH2 plays a central role in the liver to metabolize ethanol. With the common E487K variant, there is a deficiency of ALDH2 function; when ethanol is consumed, there is a systemic accumulation of acetaldehyde, an intermediate product in ethanol metabolism. In ALDH2 deficient individuals, ethanol consumption acutely causes the “Alcohol Flushing Syndrome” wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 100 publications
0
0
0
Order By: Relevance
“…An underlying explanation for this disparity among populations is the genetic sensitivity to alcohol's effect on PCa risk [24]. It is reported that the carrier rate of hereditary disorder aldehyde dehydrogenase 2 (ALDH2) deficiency is much higher in East Asians compared to Europeans [25]. A high probability of carrying ALDH2 deficiency combined with frequent alcohol consumption may result in a greater excess risk for PCa in individuals of East Asian ancestry.…”
Section: Discussionmentioning
confidence: 99%
“…An underlying explanation for this disparity among populations is the genetic sensitivity to alcohol's effect on PCa risk [24]. It is reported that the carrier rate of hereditary disorder aldehyde dehydrogenase 2 (ALDH2) deficiency is much higher in East Asians compared to Europeans [25]. A high probability of carrying ALDH2 deficiency combined with frequent alcohol consumption may result in a greater excess risk for PCa in individuals of East Asian ancestry.…”
Section: Discussionmentioning
confidence: 99%